Adsorption separation of R134a, R125, and R143a fluorocarbon mixtures using 13X and surface modified 5A zeolites - Wanigarathna, Darshika Kumari Juwan Arachchillage (2020)
We report a facile method for the adsorption separation of fluorocarbon blends containing tetrafluoroethane (R134a), pentafluoroethane (R125) and trifluoroethane (R143a) refrigerants into their pure components using commercial 13X zeolite and pore-size modified 5A zeolite under ambient condition. Based on the measured R134a, R125, and R143a pure gas equilibrium adsorption isotherms, the adsorption capacity varies in the order of R134a > R143a > R125 on 13X zeolite. The mixed gas breakthrough experiments reveal that 13X zeolite selectively adsorbs R134a over R125 and R143a. By running two adsorption cycles, it is possible to obtain R134a with ultrahigh purity. Furthermore, through chemical modification of tetraethyl orthosilicate (TEOS), the pore size of 5A zeolite could be successfully narrowed to the extent to just adsorb R125 while excluding R143a. The modified 5A zeolite was utilized to separate refrigerant mixtures containing R125 and R143a into their pure components.